Galaxy Cybercafe / Thomas Baos … [et al.] - Baos, Thomas; Lanchang, Kereen Samban; Sulainan, Sheril Nur Haziani (2017)
This report was commissioned to investigate the problem faced by Summer PC and to recommend ways to curb the problems since their opening on August 2017. This is important to be a guideline for our business plan report. The study draws attention as they having a problem in operating good computer software. The main product of their business is computer equipment so it is expected that they have good computer operating system. However, it seems that they have difficulty in maintaining the computer system as they have 98 computers in total. Sudden crash and shut down unexpectedly can become the factors decreasing in customers. Further interviews reveal that the location of the premise is not actually strategic. The Summer Mall divided into west and east wings. The premises located at the east wing which is the blind spot area in the mall. Difficulty in searching the premise becomes a huge problem for new costumer to reach the premise. Summer PC is the only cybercafe that located in Samarahan area. This is a gold opportunity for them to further their business. This report conclude that this is an ideal type of business that could satisfy the new customer demand since cybercafe is significant for online gaming and searching information. It is recommended that Summer PC take immediate measures to update the latest version of the computer software. This need to be taken seriously as the computer is their main product. In addition they must make a banner to promote their premise at the entry of the mall so that new customer can locate their premise easily. It is suggested that they promote their premise more often in the social media such as Facebook page.